Two Rival Newly Fabricated Potentiometric Sensors to Enhance Selectivity Toward Cu(II) Ions - Gamal Abdel-Hafiz Mostafa; Hazem Mohamed Abu Shawish; Salman Mustafa Saadeh; Essam Ezzeldin (Indonesian Journal of Chemistry, 2021)
Utilizing the well-known ability of Schiff base ligands to bind metal ions, two newly fabricated ligands, namely: 2-((2-hydroxybenzylidene)amino)benzoic acid (L1) and 2-(furan-2-ylmethyleneamino)phenol (L2) were employed to coordinate copper(II) (Cu(II)) producing the characteristically stable complexes that performed as the ionophores in the presently fabricated electrodes A and B. Thus it was possible to build these electrodes that have attractive properties and expected behavior, namely, low detection limits: 2.32 × 10–7 and 1.14 × 10–6 M Cu(II), Nernstian slope of 29.13 and 30.85 mV/decade Cu(II), broad concentration ranges from 3.98 × 10–7–1.00 × 10–2 and 1.52 × 10–6–1.00 × 10–2 M for sensors A and B, respectively, as well as short response time (ca. 3–5 s) with distinct selectivity toward Cu(II) over the other cations and applicability over the pH range 1.5–5.5 for miscellaneous samples: aqueous solutions, urine, and blood serum. Thus, these sensors surpass many others towards fulfilling the intended function of Cu(II) determination in various applications.